2018
DOI: 10.21500/20112084.3373
|View full text |Cite
|
Sign up to set email alerts
|

Desempeño cognitivo en portadores asintomáticos de las mutaciones R1031C y R141C en CADASIL

Abstract: La Arteriopatía Cerebral Autosómica Dominante con Infartos Subcorticales y Leucoencefalopatía (CADASIL), es producida por mutaciones en el gen NOTCH3, es la causa hereditaria más común de accidentes cerebrovasculares isquémicos repetidos. Objetivo: establecer el desempeño cognitivo en portadores asintomáticos con las mutaciones R1031C Y R141C. Método: estudio observacional, analítico transversal. Se dividieron en tres grupos: portadores asintomáticos con mutación R1031C (n=39), asintomáticos con mutación R141C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…Dichgans and Leys (2017) suggested that cognitive impairments of vascular origin may be associated with normal or mildly impaired daily living activities, thus defining so-called vascular mild cognitive impairment. Our study supports the idea that individuals with CADASIL might show visuoconstructional impairments without clinically relevant cognitive deterioration, suggesting that vascular mild cognitive impairment could include defects of visuoconstructional abilities (Zuluaga-Castaño et al, 2018). It often has been observed, indeed, that the burden of lacunar lesion significantly correlates with low cognitive performance in individuals with CADASIL (Chabriat et al, 2009), but few studies have specifically searched for visuoconstructional impairments, which can go unnoticed because they are less salient than other cognitive defects.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Dichgans and Leys (2017) suggested that cognitive impairments of vascular origin may be associated with normal or mildly impaired daily living activities, thus defining so-called vascular mild cognitive impairment. Our study supports the idea that individuals with CADASIL might show visuoconstructional impairments without clinically relevant cognitive deterioration, suggesting that vascular mild cognitive impairment could include defects of visuoconstructional abilities (Zuluaga-Castaño et al, 2018). It often has been observed, indeed, that the burden of lacunar lesion significantly correlates with low cognitive performance in individuals with CADASIL (Chabriat et al, 2009), but few studies have specifically searched for visuoconstructional impairments, which can go unnoticed because they are less salient than other cognitive defects.…”
Section: Discussionsupporting
confidence: 87%
“…Only a few researchers have investigated constructional apraxia (CA)—that is, the inability to produce a complex figure by putting its parts in the correct spatial relationship (Kleist, 1934), occurring in visuoconstructional tests—in individuals with CADASIL (Zuluaga-Castaño et al, 2018). CA has been reported in individuals who are affected by cognitive deterioration (Da Silva et al, 2011; Song et al, 2014), but such impairments can also occur independently from general cognitive impairment.…”
mentioning
confidence: 99%